Faktor-Faktor yang Berhubungan dengan Demam Berdarah Dengue pada Anak yang Dirawat Inap di RSUD Labuang Baji Makassar Tahun 2022 - Amalia, Firda; Saleh , Adriandy; Amiruddin, Tedy (Fakultas Kedokteran Universitas Bosowa, 2023)
Dengue fever (DHF) is a second common medical condition highly prevalent in Central America, the Americas, the Caribbean and Southeast Asia. Humans are the pathogen and natural host of DHF. The dengue virus is part of the Flavivirus and Flaviviridae family. Insect bites, mainly Aedes aegypte and Aedes albopictus, are widespread in most parts of Indonesia. Dengue fever is most common in the age group of 5-14 years. The purpose of this study was to determine the factors that have an association with dengue hemorrhagic fever in children hospitalized at Labuang Baji Hospital Makassar in 2022. The research sample used was total sampling with a sample size of 38 people recorded in medical records. This research is cross sectional with analytic research design. Data analysis was processed using bivariate analysis, namely the chi-square test. The results showed that as many as 38 medical records of pediatric patients, 32 (84.2%) people who experienced DHF and 6 (15.8%) people who did not experience DHF. It can be concluded that the majority of dengue hemorrhagic fever occurs at the age of 5-14 years (68.4%) and obtained a p-value of 0.000. The gender of dengue hemorrhagic fever patients in children was mostly found in males (71.1%) with a p-value of 0.000. The nutritional status of dengue hemorrhagic fever patients in children was found to be more in poor nutritional status (57.9%) and the p-value was 0.003. The study concluded that age, gender, and nutritional status have a significant relationship with the incidence of dengue hemorrhagic fever